GUP-corrected ΛCDM cosmology - Salih Kibaroğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, we investigate the effect of the generalized uncertainty principle on the ΛCDM cosmological model. Using quantum corrected Unruh effect and Verlinde’s entropic gravity idea, we find Planck-scale corrected Friedmann equations with a cosmological constant. These results modify the ΛCDM cosmology.